Small-angle neutron scattering contrast variation studies of biological complexes: Challenges and triumphs. (June 2022) - Krueger, Susan
Abstract: Small-angle neutron scattering (SANS) has been a beneficial tool for studying the structure of biological macromolecules in solution for several decades. Continued improvements in sample preparation techniques, including deuterium labeling, neutron instrumentation and complementary techniques such as small-angle x-ray scattering (SAXS), cryo-EM, NMR and x-ray crystallography, along with the availability of more powerful structure prediction algorithms and computational resources has made SANS more important than ever as a means to obtain unique information on the structure of biological complexes in solution. In particular, the contrast variation (CV) technique, which requires a large commitment in both sample preparation and measurement time, has become more practical with the advent of these improved resources. Here, challenges and recent triumphs as well as future prospects are discussed.